Bionomics and control of Glossina austeni and G.brevipalpis (Diptera : Glossinidae) in South Africa - Van den Bossche, Peter (University of Pretoria, 2013)
Thesis (PhD (Veterinary Tropical Diseases))--University of Pretoria, 2008.